CARDIOPROTECTIVE ACTIVITY OF EMPAGLIFLOZIN AND LINAGLIPTIN WITH OR WITHOUT METFORMIN IN DIABETIC RATS INDUCED WITH ACUTE MYOCARDIAL INFARCTION - Hasna Fadhilah, Zahra
Recently, many new classes of anti-diabetic agents have been studied, such as sodium glucose co-transporter-2 inhibitors (SGLT-2i) and dipeptidyl peptidase-4 inhibitors (DPP-4i) which are proven to have protection against heart damage. This study aims to determine the effect of the combination of these drug classes on the parameters of acute DM and IM with or without the addition of metformin which is the first-line drug for type 2 DM patients. Type 2 DM models were made by intragastric induction of Lipomed® 20% MCT/LCT 20 mL/KgBB. (i.g) for 14 days, followed by induction of streptozotocin (STZ) 55 mg/KgBW intraperitoneally (i.p). Next, the IM model was created by induction of isoproterenol 85 mg/KgBW i.p on days 29 and 30. Animals were divided into 7 groups. Negative control group (Na CMC 0.5% i.g), positive control group DM+IM, test group 1 (empagliflozin 1 mg/KgBB i.g), test group 2 (linagliptin 0.5 mg/KgBB i.g), test group 3 ( metformin 87.8 mg/KgBB i.g), test group 4 (a combination of empagliflozin and linagliptin), and test group 5 (a combination of empagliflozin and linagliptin with the addition of metformin) for 30 days. The combination group without the addition of metformin showed improvement in DM parameters (KITT values 1,00%/minute and GDP 123.33 mg/dL) and IM with inhibition percentage (%) increased biomarkers creatine kinase (CK), CK-MB, aspartate transaminase (AST). ), and alanine transaminase (ALT) respectively, namely, 62.37; 63.84; 48.42; and 42.41. In histopathological observation, tight gaps between myocardial fibers were observed and no inflammatory cell infiltration was observed in determining the % area of infarction with imageJ, it gave a lower result of 2.94%. Not only that, administering this drug combination was proven to increase SIRT-1 protein levels by 7.25 ng/mL. Whereas the combination with the addition of metformin did not give a better effect than the previous combination on DM parameters (KITT value 0.89%/minute and GDP 160.67 mg/dL) and IM with the percentage of inhibition (%) increased biomarkers sequentially, namely, 56 .33; 57.57; 35.27; and 36.83. In histopathological observations, wide gaps between myocardial fibers were still observed, as well as inflammatory cell infiltration, and determining the % area of the infarct using ImageJ gave a greater result of 3.48%. Not only that, the SIRT-1 protein level detected was less, namely 5.44 ng/mL. So it can be concluded that administering the combination of empagliflozin and linagliptin without the addition of metformin provides better protection in acute IM conditions due to DM.